Intramolecular Diels–Alder Furan-Mediated Synthesis of 8-Aryl-3,4-di-hydroisoquinolin-1(2H)-ones, Convenient Precursors of Indeno[1,2,3-ij]isoquinolines - Treus, Mónica; Harwood, Laurence M.; Estévez, Juan C.; Salas, Cristian; Drew, Michael G. B.; Estévez, Ramón J. (Synlett, 2013)
We describe herein preliminary studies on the intramolecular Diels–Alder furan-mediated synthesis of 8-aryl-3,4-dihydroisoquinolin-1(2H)-ones that constitutes a new, formal synthesis of indeno[1,2,3-ij]isoquinolines.
Keywords: alkaloids; 8-arylisoquinolines; indeno[1,2,3-ij]isoquinolines; Bischler–Napieralski cyclization; intramolecular Diels–Alder furan reaction